MANAJEMEN PELAYANAN PUBLIK (Studi Kasus Rumah Susun Sederhana Sewa Di Kelurahan Ujuna Kecamatan Palu Barat, Kota Palu) - Jamaluddin, Indar Ismail (Katalogis, 2016)
Simple Flat (Rusunawa) Ujuna has not completely targeted to inhabitants of low-income communities (MBR). On the other hand, inhabitants of MBR have many rent arrears. This study aims to know the functions of public service management at the first built simple flat in Palu City. The type of research is qualitative descriptive. The results of the study, the planning function indicates that it has not been compatibility between the program of manager with the wishes of the inhabitants. In organizing function has happened the working relationship between managers, as well as the Head of Rusunawa has delegated his authority to some employees believed. The function of management, to motivate technical managers are interpreted by the Head of Rusunawa in the form of meetings and directives based on the guidelines and socialization of ministries that is subsequently adjusted to the conditions of Rusunawa Ujuna. The technical managers just graduated senior high school and junior high school with salary under minimum wage as well as have not followed the training. While the function of monitoring, there has been clear about reward and sanction against the manager of flats. In addition, the orientation of managers is in financial report, instead of improving the quality of the program, while the department does not control it.